Detection of Tetracycline Resistance Genes among Escherichia coli Isolated from Layer and Broiler Breeders in West Java, Indonesia - A. Indrawati; K. Khoirani; S. Setiyaningsih; U. Affif; Safika; S. G. Ningrum (Faculty of Animal Science, Bogor Agricultural University, 2021)
A major current problem in public health is the issue of antimicrobial resistance of Escherichia coli in humans and poultry. In Indonesia, multidrug-resistant E. coli are of specific concern since such E. coli may cause public health problems in humans. The prevalence of multidrug-resistant chicken E. coli strains and the E. coli resistance genes, which are tet(A) and tet(B) genes, were investigated in the present study. A total of 57 swabs were collected from layer and broiler breeder farms in West Java, Indonesia, and used in the experiment. Eighteen isolates were identified as E. coli by the disk diffusion method. The isolates classified as drug-resistant and intermediate were then identified using PCR for the antimicrobial resistance genes. The results showed that 18 isolates of E. coli from layer-breeder and broiler-breeder farms in West Java were resistant to ampicillin (100%), nalidixic acid (94%), tetracycline (88%), oxytetracycline (83%), gentamicin (27%), and chloramphenicol (22%). PCR identification of E. coli antimicrobial-resistant genes in 18 isolates showed tet(A) and tet(B) genes. This study reports antimicrobial resistance genes among E. coli on layer and broiler breeder farms in West Java. This present study showed that E. coli isolated from layers-breeder and broiler-breeder farms in West Java of Indonesia carried tet(A) and tet(B) genes, the multidrug-resistance genes.